PRAGMATIC ANALYSIS OF THE USE OF INDONESIAN BLASPHEMY CASES IN BAP SINGKAWANG POLICE INVESTIGATORS - Dedy Ari Asfar; Ahadi Sulissusiawan; Antonius Totok Priyadi (Sean Institute, 2023)
This study aims to examine the use of speech containing blasphemy in the examination minutes (BAP) of Singkawang Police investigators with a pragmatic approach. Blasphemy is one language with legal impact in the form of degrading religious beliefs. This study used a qualitative descriptive approach. The data collection technique used in this study was indirect techniques with documentary studies because the data was obtained through examination minutes documents (BAP) owned by Singkawang Resort police investigators. The analytical approach used in this study is pragmatic. As a result, there are type of directive speech act with 3 functions: questioning, suggesting, and prohibiting. Then, the assertive speech act has 2 parts: claiming the truth and complaining. Also, the type of expressive speech act has 1 function, namely the blame function. These functions contain the meaning of blasphemy to the religious beliefs of Muslims.